2021
DOI: 10.47197/retos.v42i0.87421
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de un programa de juegos pueriles sobre la coordinación motriz en estudiantes de educación básica (Incidence of a childish games program on motor coordination in students of basic education)

Abstract: Resumen La estructura corporal del escolar con edad entre los siete y ocho años está en un continuo crecer y el maestro de educación física puede constituirse en un factor para potencializar el desarrollo de su Coordinación Motriz (CM); por medio de programas de intervención podría ayudar a mejorar sus competencias físicas, sociales y académicas. Este trabajo investigativo tuvo por objetivo, establecer la incidencia de un programa de juegos pueriles sobre tal coordinación en una muestra de 96 alumnos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…The relationship between factors found a strong positive relationship between bimanual performance and the unimanual abilities of the affected hand and sensory impairments may occur independently of motor impairments (Burbano Pantoja, Cárdenas Remolina, & Valdivieso Miranda, 2021;Villafane, Cantero-Tellez, & Berjano, 2019). It has been suggested that a child with CP may have a greater disability in ADL function than a standardized test might suggest (Gordon & Duff, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between factors found a strong positive relationship between bimanual performance and the unimanual abilities of the affected hand and sensory impairments may occur independently of motor impairments (Burbano Pantoja, Cárdenas Remolina, & Valdivieso Miranda, 2021;Villafane, Cantero-Tellez, & Berjano, 2019). It has been suggested that a child with CP may have a greater disability in ADL function than a standardized test might suggest (Gordon & Duff, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Biomechanics in the didactics of body percussion has a very important role in structuring the movements and above all demonstrating that the activities of the BAPNE method are not harmful (Aedo-Muñoz et al, 2021;Alonso-Marco & Romero-Naranjo, 2022;Bermejo-Frutos, 2014;Burbano-Pantoja et al, 2021;Cadenas-Sánchez et al, 2015). Similarly, there are already proposals on body percussion and body schema in the sciences of physical activity and sport.…”
Section: Body Percussion In Physical Activity and Sport Sciencesmentioning
confidence: 99%
“…Allí, el dinamismo y eficiencia con el que ejecute dichas acciones dependerá de que tan activo y consciente sea ese movimiento como proyección de su cuerpo (Backes, Porta & Difabio De Anglat, 2015). En consecuencia, se revela la importancia que tiene la coordinación motriz en el desa-rrollo del infante como sujeto activo de la sociedad (Villa de Gregorio, Ruiz Pérez & Barriopedro Moro, 2019;Burbano Pantoja, Ángel, Cárdenas Remolina & Valdivieso Miranda, 2021).…”
Section: Introductionunclassified